Etnografia na praça república da Bolívia em Campo Grande -MS: o evento Praça Bolívia - ISABELLE JABLONSKI (2021)
This dissertation seeks to understand – from an ethnographic perspective – the social senses of the Bolivia Square Event, also known as “Feirinha da Bolívia”, that happens at the Republic of Bolivia Square in Campo Grande (MS). With data produced in the field (during the year of 2019) from interviews, participant observations and informal conversations, this work seeks to reflect about how the Bolivia Square Event gains meaning through symbolic and social agencies of difference (ethnic, cultural, political or social). The street market workers – and other agents responsible for organizing the event – mobilize different representations about otherness to build it as distinct, authentic or exclusive. The dissertation demonstrates how this symbolic construction dialogues with the new grammars of consumption within capitalism as well as with the class divisions that cross contemporary society. It allows us to visualize ethnographically how the creation of a new form of a traditional event – the street market – takes place in relation to the reproduction of more general social and symbolic structures.